Contested volumetric space: floor area uplift policy in Jakarta - Herlambang, Suryono; Astuti, Wahyu; Suryadjaja, Regina (Bulletin of Geography. Socio-economic Series, 2022)
This paper illustrates how the extraction of land value into volumetric spaces (subterranean spaces, elevated infrastructures and high-rise buildings) is rendered possible through accumulation strategies embedded in spatial planning in Jakarta. In doing so, it carefully delves into the shift in Floor-Area Uplift (FAU) compensation policy and its relationship with the expansion of mass transportation system development. We analysed urban planning and high-rise building policy documents from 1975–2017 and modelled the allowable FAU based on those policies. We illustrate, first, the transformation of FAU discourse in urban policies and how its operability is facilitated in discretionary planning regimes. This paper then demonstrates the planning gain delivery and consequences produced through FAU compensation policy. We argued how volumetric urbanism in Jakarta had been produced and sustained through entrepreneurial motives. It continues to segregate the city both in local and urban contexts despite its positivist development goals.